Avoiding the pathologizing of children of prisoners. (September 2016) - Knudsen, Else Marie
Using the existing empirical literature and making reference to original research with Canadian children of prisoners, this Practice Note offers a caution to practitioners against making homogenizing or pathologizing assumptions about children who have a parent involved in the criminal justice system. Specifically, the notions that children of prisoners are highly likely to follow their parent to prison, are identical in their experiences of parental incarceration, or are necessarily in need of a specific counselling intervention are challenged. While children with a parent in prison are vulnerable to a variety of risk factors such as poverty, the relationship between parental incarceration, its covariates, and negative outcomes is complex. This paper concludes with four recommendations to practitioners working with families of prisoners and others involved in the justice system.